The Return of Pancasila: Political and Legal Rhetoric Against Transnational Islamist Imposition - Yance Arizona (The Constitutional Court of the Republic of Indonesia, 2019)
The rise of transnational Islamist movements in Indonesia in the last two decades recurrences the old debate between Pancasila and Islamism. This kind of fundamental Islamic movements widespread with their conservative view and it has had detrimental effects on the Indonesian society’s social cohesion. President Joko Widodo seeks to revive Pancasila to confront this threat. This is not for the first time Pancasila is used by the Indonesian government to resolve the tension between Islamic values and nation-state principles. Both President Sukarno and Suharto also used Pancasila as a vehicle to discipline their political opponents. Adopting a non-essentialist approach to Pancasila, I argue that the return of Pancasila in recent years would be more complicated because of the narrative of Pancasila revivalism as an adversarial ideology is bounded by traditionalism and lack of progressive interpretation. Instead of locating Pancasila as the counterpart to Islamism, what is needed is re-interpretation of Pancasila as a unifying ideology.